The Psychogeographies of Site-Specific Art - Shana MacDonald (Media Theory)
Contemporary efforts at urban revitalization have encouraged an increased production of site-specific public art events that temporarily inhabit popular city hubs. These â€œpop upâ€ interventions range from loosely assembled happenings to the more institutionally supported all-night art festivals like Nuit Blanche. This paper examines the types of geospatial memory produced and inscribed through small-scale, participatory, site-specific urban art events. It considers how this work participates in forms of placemaking which both enact provisional and iterative forms of assembly while also marking the psychogeographic remains of space. Taking up examples from SensoriuM lab (Montreal) and Mobile Art Studio (Kitchener), the paper suggests how public art may be used to elicit performance-based and participatory geospatial media that maps residentsâ€™ embodied and historied relationship to urban space.